Islamic spirituality and its impact on life as a Muslim - Mohd Amin, Wan Mohd Azam; Ahmad, Masitoh; Abdul Rahim, Adibah (IIUM Press, 2018)
This paper offers observations on the concept of Islamic spirituality, its scope and its significance in the well-being of man. The authors highlight the discussion on the concept of man and the human soul, and his relationship with God and the universe as a basic framework of Islamic spirituality. The framework is in accordance with the Qur‘ān, the Sunnah of the Prophet (p.b.u.h), and the consensus of religious scholars (‗ulamā‘). This research is qualitative, in which a textual analysis technique is applied on classical, as well as relevant contemporary materials on Islamic spirituality. Findings show that the well-being of a Muslim and the sustainability of his living depend on some fundamental principles, such as the unity of God (tawḥῑd), the vicegerent of God (khalīfatu‗Llah), godconsciousness (iḥsan) and others. These principles constitute as core manifestations of Islamic spirituality as evident from the life of Prophet Muhammad (p.b.u.h)